Effects of Biodegradable Polymers on the Rat’s Damaged SpinalCord Neural Membranes: Effects of biodegradable polymers on neural membranes - Falahati, Mojtaba; Mobasheri, Hamid (Iranian Journal of Pharmaceutical Sciences, 2008)
The overall goal of this study was to identify the appropriate biomaterials ableto facilitate the regeneration in rat’s injured adult spinal cord. Acute damage to axonsis manifested as a breach in their membranes, ionexchange distortion across thecompromised region, local depolarization and even conduction block. It would beof particular importance to interrupt the progress of events happening after acuteinjury to the spinal cord. Repair strategies using transplants of cells have shown manyattractions in spinal cord repair studies. However, as the processes of purificationand growth require time, they cannot be fully implemented in acute injuries.Furthermore, application of cell grafts from other human or animal sources are likelyto provoke immune reactions in human patients. Immediate repairing or sealing theregions of compromised membrane with hydrophilic polymers or surfactants couldretard or reverse the permeabilization of nerve fiber membranes. Biodegradablepolymeric materials used for tissue engineering, made of either peptide or non-peptidecomponents, are considered as potential candidates. Application of the hydrophilicpolymer, polyethylene glycol (PEG), has showed to be effective in the repair of nervemembrane damage associated with severe spinal cord injury in adult rat. This classof large hydrophilic molecules can reverse the permeabilization of ruptured cellmembranes as well as anatomically reconnect their severed processes. Our preliminaryresults showed rather rapid partial restoration of the declined magnitude of compoundactions potentials (CAPs) in injured spinal cords, varying as a result of theintroduction of PEG’s with different molecular weights.